2022
DOI: 10.1186/s13052-022-01390-8
|View full text |Cite
|
Sign up to set email alerts
|

The awareness and acceptance of anti-COVID 19 vaccination in adolescence

Abstract: Background COVID-19 had devastating effects on children’s and adolescents’ life, including neuropsychological impairment, discontinuation of social life and education. Since June 2021, antiCOVID19 vaccination has become available to adolescents in Italy up to 12 years and since December 2021 to children aged more than 5 years. The pediatric population represents a challenging target for vaccination. Aim of the study is to perform a survey among adolescents to explore factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…The results of this pilot survey show that in Italy, about four months after the Italian government authorized the immunization campaign even for adolescents, a positive attitude toward vaccination can be found, versus only around 8% of the sample rejecting it. This is consistent with the data reported by the Italian government during the time of this study [ 47 ], and with the rates observed in previous studies [ 29 , 48 ]. In addition, it is also worth mentioning that vaccination for COVID-19 was not mandatory for this age group and that, at the time of the survey, individuals who wanted to get vaccinated possibly could not do it right away due to long waiting lists.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this pilot survey show that in Italy, about four months after the Italian government authorized the immunization campaign even for adolescents, a positive attitude toward vaccination can be found, versus only around 8% of the sample rejecting it. This is consistent with the data reported by the Italian government during the time of this study [ 47 ], and with the rates observed in previous studies [ 29 , 48 ]. In addition, it is also worth mentioning that vaccination for COVID-19 was not mandatory for this age group and that, at the time of the survey, individuals who wanted to get vaccinated possibly could not do it right away due to long waiting lists.…”
Section: Discussionsupporting
confidence: 94%
“…Research involving medium to large samples has not found an association with socio-demographic variables [ 22 , 29 , 48 ], or if it has, it is that being female has been positively associated with a higher likelihood of being hesitant about the vaccine, as in a study conducted on this matter in China [ 49 ]. More studies would be needed to explore any influence of gender differences, mostly investigated in adults [ 50 ], and education type, on the intention to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that parents’ decisions and attitudes are directly related to the immunization status of adolescents [ 26 ]. However, in the case of a minor who would get the vaccination but one or both parents do not agree, the orientation of jurisprudence is that a judge can temporarily “suspend” the ability of a parent opposed to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Mogući je razlog takvim stavovima liječnika to što u svom svakodnevnom poslu svojim bolesnicima približavaju zdravstvene informacije, a studenti, iako vjerojatno imaju veće teorijsko znanje, nemaju dovoljno praktičnog kliničkog iskustva. 13,[15][16][17][18] Od ukupnog broja ispitivanih studenata i liječnika obiteljske medicine, 60% ih je bilo cijepljeno protiv bolesti COVID-19. Procijepljenost protiv bolesti COVID-19 među ispitanicima, bilo studentima, bilo liječnicima, koji su cijepljeni protiv gripe ove ili prethodnih sezona, bila je veća u odnosu na one koji se nikada nisu cijepili protiv gripe.…”
Section: Raspravaunclassified